A Positive Causal Influence of IL-18 Levels on the Risk of T2DM: A Mendelian Randomization Study - Zhuang, He; Han, Junwei; Cheng, Liang; Liu, Shu-Lin (Frontiers in Genetics, 2019)
A large number of clinical observations have shown that interleukin-18 (IL-18) plasma levels are positively correlated with the pathogenesis and development of type 2 diabetes mellitus (T2DM), but it remains unclear whether IL-18 may cause T2DM, primarily due to the influence of reverse causality and residual confounding factors. Genome-wide association studies (GWAS) have led to the discovery of numerous common variants associated with IL-18 and T2DM and opened unprecedented opportunities for investigating the possible associations between genetic traits and diseases. In this study, we employed a two-sample Mendelian randomization (MR) method to analyze the causal relationships between IL-18 plasma levels and T2DM using IL18-related SNPs as genetic instrumental variables (IVs). We first selected eight SNPs that were significantly associated with IL-18 but independent of T2DM. We then used these SNPs as IVs to evaluate their effects on T2DM using the inverse-variance weighted (IVW) method. Finally, we applied the sensitivity analysis and MR-egger regression to evaluate the heterogeneity and pleiotropic effects of each variant, respectively. The results based on the IVW method demonstrated that high plasma IL-18 levels significantly increase the risk of T2DM, and no heterogeneity or pleiotropic effects appeared after the sensitivity and MR-egger analysis.